L'utilisation de mót anglais dán un périodique réservé aux adolescents Vietnamiens. Conséquences sur L'apprentissage du Francais : - Nguyen, Thanh Tong (Universite de Can Tho, 2010)
This research paper examines the effects of borrowed words from English on French teaching in Vietnam. The data analysis shows that the teaching and learning French today have a lot of difficulties.